2020
DOI: 10.25258/ijddt.10.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Simple Colorimetric Determination of Dexamethasone

Abstract: A simple, environmentally benign, cost-effective, and sensitive colorimetric determination for the pharmaceutical drug dexamethasone sodium phosphate (DXP) has been developed by the formation of a colored complex with fluoranil. The process was sensitive and linear over the range 1 to 40 μg/mL, excellent correlation coefficient 0.9989, recovery% 99.80 ± 1.3, limit of detection (LOD) and limit of quantification (LOQ) were 0.23 and 0.9 μg/mL, respectively, and good RSD ~1.63%. The experimental conditions were op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…e measurement results show the maximum readable dexamethasone at a wavelength of 483 nm. is is close to the following literature which shows that the reaction of dexamethasone-hydroxylamine complex and fluoranyl has a maximum wavelength of 485 nm [12].…”
Section: Analysis Of Dexamethasone In Herbal Medicine Samplesupporting
confidence: 91%
See 3 more Smart Citations
“…e measurement results show the maximum readable dexamethasone at a wavelength of 483 nm. is is close to the following literature which shows that the reaction of dexamethasone-hydroxylamine complex and fluoranyl has a maximum wavelength of 485 nm [12].…”
Section: Analysis Of Dexamethasone In Herbal Medicine Samplesupporting
confidence: 91%
“…e results of the percent recovery in Table 1 showed that the best conditions were when the addition of hydroxylamine hydrochloride was 20 mg and the best reflux time was 60 minutes. It is because of the less reflux time used, the complex reaction between dexamethasone and hydroxylamine has not been maximally formed and there are still residual substances that have not reacted, but on the other hand, if the reflux time is too long, the complex reaction that has been formed will slowly be degraded [12,17].…”
Section: Optimization Of Optimum Conditions and Time For The Formatio...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, spectrophotometric as well as colorimetric approaches are considered environmentally benign compared to other sophisticated analytical techniques. [ 14 15 16 17 ] Cefdinir was determined likewise by 0 and first-order derivative spectrophotometry. [ 18 ] While in another study, the approach of Taguchi experimental design was used for a spectrofluorometric determination of cefdinir.…”
Section: Introductionmentioning
confidence: 99%